Efeito de enzimas na digestibilidade ruminal e perda de matéria seca da silagem do grão de milho reidratado - Lopes, Naina Magalhães (2016)
Three experiments evaluated the addition of enzymes to increase the ruminal in vitro digestibility of mature ground corn, rehydrated, and ensiled (REC). The effects of particle size (PS; fine or coarse), duration of storage (D), and type of endosperm (H; flint or floury) were also evaluated. In Exp. 1, treatments Control, α Amylase 1, and α Amylase 2 with Control, Amyloglucosidase 1, Protease 1, and Fibrolytic, stored for 81 d. In Exp. 2 was evaluated the effects of H, PS, enzyme (α Amylase 3, Protease 2,α Amylase 3 + Protease 2) and D (30 d, 90 d, 120 d). Exp. 3 evaluated the effects of enzyme (Control, Amyloglucosidase 2), PS and D (30 d, 250 d). The most promising enzymes for improving REC digestibility were amyloglucosidase and protease. Amyloglucosidase increased the size of the fast digestible fraction and the effective ruminal degradation. However, this enzyme increase the loss of DM during ensiling and reduced starch concentration in feed. Protease reduced the content of prolamin in REC and increased the fractional degradation rate and the effective ruminal degradation.